Developing scientific entrepreneurship and complex thinking skills: creating narrative scripts using ChatGPT - George-Reyes, Carlos Enrique; Vilhunen, Elisa; Avello-Martínez, Raidell; López-Caudana, Edgar (Frontiers in Education, 2024)
The increased access to artificial intelligence (AI) applications has made it possible to develop more engaging and complex educational activities for students in different disciplines. This research explored expanding university students' knowledge of scientific entrepreneurship skills using an Artificial Intelligence application. The students participated in a training experience using the conversational ChatGPT language model to generate narrative scripts for various topics on scientific discoveries and technological advances to create new products or services that offer cost-effective solutions based on science. The experience was designed employing the i4C model (identify, ideate, invent, inform). The study used a two-sample design with repeated measurements based on a pre-test and post-test. One hundred five graduate students from two master's degree programs at the Bolivarian University of Ecuador participated during the 2022-2023 academic period. The results indicate that the students notably improved in acquiring the knowledge necessary for scientific entrepreneurial skills. The study concluded that applying AI ChatGPT with a narrative scripting strategy can create new learning opportunities for students.